Politeness Strategies of the General Practitioners at Community Health Center in Semarang - Kartini Rahayu; Muhammad Suryadi (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2019)
Communication which occurs between general practitioners and patients is meant to meet the patient's medical needs. In carrying out communication, general practitioners and patients always pay attention to their speech in order to reduce the threat of the face of the hearer and to establish a good relationship. Based on this, this study examines the use of general practitioners' politeness strategies in community health centers and aims to describe the politeness strategies used by general practitioners in establishing communication with patients. This politeness strategy study is a qualitative descriptive research in which data were obtained through the observation method and then were analyzed. The results of data analysis showed that general practitioners used three Brown and Levinson’s politeness strategies, namely Bald on Record strategies, positive politeness strategies, and negative politeness strategies.